Lenalidomide or bortezomib as maintenance treatment remedy the inferior impact of high-risk cytogenetic abnormalities in non-transplant patients with newly diagnosed multiple myeloma: a real-world multi-centered study in China - Zhuang, Zhe; Tian, Ying; Shi, Lei; Zou, Dongmei; Feng, Ru; Tian, Wei-wei; Yu, Hong; Dong, Fei; Liao, Aijun; Ma, Yanping; Liu, Qinhua; Liu, Shuangjiao; et al. (Frontiers in Oncology, 2023)
Maintenance treatment is a pivotal part in the whole process management of multiple myeloma (MM), which further deepens response and improves survival. However, evidence of maintenance in non-transplant MM patients is inadequate in the real-world practice. Here we retrospectively analyzed the efficacy and survival in 375 non-transplant MM patients from 11 centers between 2010 and 2021 in north China. There were 141, 79 or 155 patients receiving lenalidomide (L-MT), bortezomib (B-MT) or thalidomide (T-MT) maintenance respectively after a median 7 cycles of front-line regimens. Patients on L-MT and B-MT had significantly greater proportions of high-risk cytogenetic abnormalities (HRCAs) detected by fluorescence in situ hybridization (FISH), which defined as 1q21 gain, 17p deletion, adverse immunoglobulin heavy chain (IgH) translocations. Though the progression-free survival (PFS) and overall survival (OS) were comparable among three groups, L-MT and B-MT remedied the negative impact of HRCAs on survival (PFS: L-MT 26.9m vs 39.2m, p=0.19; B-MT 20.0m vs 29.7m, p=0.36; both OS not reached). Patients with HRCAs in T-MT group presented inferior clinical outcome to standard-risk patients (PFS: 12.1m vs 22.8m, p=0.02, HR=1.8, 95%CI 1.0-3.4; OS: 54.9m vs NR, p＜0.001, HR=3.2, 95%CI 1.5-7.0). Achieving complete response (CR) after induction therapy led to superior PFS compared to other degree of response, regardless of maintenance medication. Furthermore, maintenance duration over 24months correlated with favorable survival. Due to the large gap of transplant eligibility in China, optimizing maintenance therapy is important to non-transplant MM patients. In this real-world multi-centered study, our findings suggest that clinicians prefer to prescribe lenalidomide or bortezomib as maintenance therapy in high-risk settings, which are superior to thalidomide in non-transplant MM patients. Achievement of CR and maintenance duration over 2 years were positive influencing factors on survival.